2005
DOI: 10.1213/01.ane.0000153010.49776.e5
|View full text |Cite
|
Sign up to set email alerts
|

Patient Satisfaction and Information Gain After the Preanesthetic Visit: A Comparison of Face-to-Face Interview, Brochure, and Video

Abstract: In this study we compared 3 methods of conducting the preanesthetic visit. We prospectively studied 197 consecutive surgical patients who were to undergo general anesthesia. The patients were randomized to a routine preanesthetic interview, a brochure plus an interview, or a self-made documentary video plus an interview. After the preanesthetic visit, the degree of patient satisfaction and information gain was quantified by a questionnaire for each method. The questions on patient satisfaction were assessed on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
79
1
8

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(94 citation statements)
references
References 27 publications
3
79
1
8
Order By: Relevance
“…A randomized study in a preanesthetic clinic showed that patient satisfaction and information gain was highest in those patients who received a documentary video when compared with a brochure or interview. 9 Similarly, at a women's cancer screening clinic, satisfaction was significantly higher among women receiving videosupported information and graphic-supported information when compared with women receiving information without teaching aids. 6 These randomized studies support the use of videotaped information over written material.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A randomized study in a preanesthetic clinic showed that patient satisfaction and information gain was highest in those patients who received a documentary video when compared with a brochure or interview. 9 Similarly, at a women's cancer screening clinic, satisfaction was significantly higher among women receiving videosupported information and graphic-supported information when compared with women receiving information without teaching aids. 6 These randomized studies support the use of videotaped information over written material.…”
Section: Discussionmentioning
confidence: 97%
“…In other medical specialties, videos have been used to help patients understand what to expect during their care, which has led to greater use of videos for patient education. 5,[7][8][9][10][11][12] Our study sought to determine if showing an ED process and patient education DVD would improve patient satisfaction, increase calls to an outpatient clinic referral line and reduce perceived waiting room times.…”
Section: Introductionmentioning
confidence: 99%
“…Perception of care is considered an essential part of patient satisfaction [1,2]. Health care includes many different components such as physical, emotional, mental, social and cultural factors.…”
mentioning
confidence: 99%
“…Questionnaires evaluated affective condition and preoperative anxiety, using the short questionnaire on current level of stress (KAB) [15] as well as selfassessment of preoperative fear [8]. Patient satisfaction was assessed immediately after the preoperative anesthesia interview (VAS 0-10).…”
Section: Data Handlingmentioning
confidence: 99%
“…Many anesthesia residents are relatively inexperienced and have received little or no specific training regarding communication with patients and might lack the skills required to communicate effectively with patients. Since preoperative anxiety is often directed towards anesthesia itself, anesthesiologists are in an excellent position to decrease patient anxiety [7,8]. Effective physician-patient interaction is sufficient to significantly reduce preoperative anxiety.…”
Section: Introductionmentioning
confidence: 99%